1984
DOI: 10.1111/j.2044-835x.1984.tb00937.x
|View full text |Cite
|
Sign up to set email alerts
|

Teachers' ratings of children's behaviour in relation to blood lead levels

Abstract: Teachers rated the behaviour of 166 children whose blood lead levels had previously been determined. Ratings were made on the Conners Scale, the Rutter Scale B(2), and Needleman's Scale. The results broadly replicated the findings of Needleman et al. (1979) in so far as they indicate a relationship between difficulties in attention and increased blood lead levels over the normal range of blood lead values. 'Hyperactivity' on the Rutter and Conners scales were found to be significantly related to children's bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
1

Year Published

1989
1989
2002
2002

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(22 citation statements)
references
References 10 publications
2
19
0
1
Order By: Relevance
“…These findings were replicated using the same rating scale on a population of children in London (33). Yule et al (33) reported a significant increase in hyperactivity, conduct problems, and inattentive/passive behavior on the Conners scale in these same children who were also impaired on the WISC-R (34). In the prospective study in children in New Zealand, Fergusson et al (62) reported increased inattention and restlessness, short attention span, and increased distractibility as functions of dentine lead in children at 8 and 9 years of age ( Table 2).…”
Section: Human Studiesmentioning
confidence: 94%
See 2 more Smart Citations
“…These findings were replicated using the same rating scale on a population of children in London (33). Yule et al (33) reported a significant increase in hyperactivity, conduct problems, and inattentive/passive behavior on the Conners scale in these same children who were also impaired on the WISC-R (34). In the prospective study in children in New Zealand, Fergusson et al (62) reported increased inattention and restlessness, short attention span, and increased distractibility as functions of dentine lead in children at 8 and 9 years of age ( Table 2).…”
Section: Human Studiesmentioning
confidence: 94%
“…In the Port Pirie study (52), all scales of the WISC-R were affected when the children were 7 years old, although the information and block design were the most sensitive. (18,28) (29) (30,31) (32) (33)(34)(35) (45), while performance at 10 years of age was most associated with lead levels at 2 years (47). Similarly, early measures in the Port Pirie study were associated with early blood lead levels (51), while performance on the MSCA at age 4 was associated with blood lead at 2 and 3 years of age but not earlier (53).…”
Section: Human Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…As is typical in studies of childhood lead exposure, blood lead was log transformed (natural log) owing to its skewed distribution. For each subscale, a regression analysis was conducted for each blood sampling time point (umbilical cord and at 6,12,18,24,30, and 36 months). In each case, sociodemographic variables (town, residence type, child's sex and ethnicity, maternal education, and sum of the 2 HOME subscales) were first entered together.…”
Section: Data Analysesmentioning
confidence: 99%
“…Subsequent studies in children selected for either high lead exposure or behavior problems showed inconsistent findings; these inconsistencies likely resulted from failure to adequately control for sociodemographic variables, such as family poverty and parenting practices, that are associated with both lead exposure3 and behavioral disturbances4 (e.g., see Needleman et al5 and Yule et al 6). …”
Section: Introductionmentioning
confidence: 99%